Guest People Hakka Identity in China and Abroad - Constable, Nicole (Studies on Ethnic Groups in China, 2014)
Open-access edition: DOI 10.6069/9780295805450 The essays in this volume analyze and compare what it means to be Hakka in a variety of sociocultural, political, geographical, and historical contexts including Malaysia, Hong Kong, Calcutta, Taiwan, and contemporary China.